2021
DOI: 10.3390/cancers13030414
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between ERAP Alleles and HLA Class I Types Support a Role of Antigen Presentation in Hodgkin Lymphoma Development

Abstract: Genetic variants in the HLA region are the strongest risk factors for developing Hodgkin lymphoma (HL), suggesting an important role for antigen presentation. This is supported by another HL-associated genomic region which contains the loci of two enzymes that process endogenous proteins to peptides to be presented by HLA class I, i.e., endoplasmic reticulum aminopeptidase 1 (ERAP1) and ERAP2. We hypothesized that ERAP and HLA class I type interact in HL susceptibility, as shown previously for several autoimmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…Unfortunately, our sample size did not allow meaningful testing of combinations of HLA alleles because of lack of statistical power. Another confounding factor is that polymorphisms in other components of the antigen presenting pathway, like ERAP1 , ERAP2 , TAP1 , and TAP2 [ 35 , 36 , 37 ], may affect antigen presentation and disrupt associations. In addition, 2-digit HLA typing defines allele groups that are highly similar but not identical, which might result in some heterogeneity within groups and therefore mask potential associations.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, our sample size did not allow meaningful testing of combinations of HLA alleles because of lack of statistical power. Another confounding factor is that polymorphisms in other components of the antigen presenting pathway, like ERAP1 , ERAP2 , TAP1 , and TAP2 [ 35 , 36 , 37 ], may affect antigen presentation and disrupt associations. In addition, 2-digit HLA typing defines allele groups that are highly similar but not identical, which might result in some heterogeneity within groups and therefore mask potential associations.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 125 cases, including 94 EBV− and 31 cHL cases for which the EBV status was unknown, were selected based on availability of sufficient DNA. Data of the original cohort on sex, age, histological subtype, HLA type, and EBV status have been published in previous studies ( 11 , 30 ). cHL diagnoses were revised according to the 2017 classification of the World Health Organization by an experienced hematopathologist ( 31 ).…”
Section: Methodsmentioning
confidence: 99%
“…ER: Endoplasmic reticulum, MHC: Major histocompatibility complex, TAP: Transporter associated with antigen processing Therefore, by modifying ERAP1 and ERAP2 activity and/or expression, ERAP SNPs have a pronounced influence on the availability and repertoire of antigenic peptides for presentation by HLA class I molecules [31], thereby influencing disease vulnerability [32]. Although these two enzymes may function individually, they may also form a heterodimer to enhance trimming efficiency.…”
Section: Figure 2: Mhc Class I Antigen Presentation Pathwaymentioning
confidence: 99%
“…Endoplasmic reticulum aminopeptidase 1 is highly polymorphic, with multiple common isoforms occurring in the general population. Functional examination revealed that ERAP1 missense SNPs affect the trimming efficiency of specific substrates [32]. Several ERAP1 SNPs are also strong expression quantitative trait loci (eQTLs) [50].…”
Section: Structure Of Erap1mentioning
confidence: 99%